Nuclear Powers in the Twenty First Century and the Dilemma of No First Use of Nuclear Weapons - Assist Prof. Dr. \ Emad Jasim Mohammed (The college of law and political science journal, 2023)
Due to the changing security environment in the twenty-first century, some of the traditional concepts of security that have prevailed in strategic studies, such as the concept of No First Use, need a systematic reassessment, this century has brought new dynamics of escalation, which may prompt nuclear powers to view their nuclear weapons as not just means of deterrence but as potentially usable tools.